Relations de cohérence en discours : critères de reconnaissance, caractérisation et articulation cohésion-cohérence - Francis Cornish (Corela)
The article deals mainly with the criteria and heuristic cues for a subset of coherence (or discourse) relations, in terms of a selection of short attested English and French texts – often without explicit connectives. The issue of the nature and types of discourse units involved in the integration via given coherence relations, and of their point of attachment, is also discussed. The article argues that, just as coherence relations can only be identified by exploiting a range of cues to textual cohesion, so the functioning of the latter can only be fully grasped by taking account of the role they play in the setting up of a discourse coherence relation (or on occasion, of more than one such relation). Textual cohesion and discourse coherence are thus complementary, and even interdependent. A critique of W.C. Mann and S.A. Thompson’s RST approach to such relations forms the basis for the discussion.